2006
DOI: 10.1111/j.1748-7692.2006.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

DOES ELASTIN CONTRIBUTE TO THE PERSISTENCE OF CORPORA ALBICANTIA IN THE OVARY OF THE COMMON DOLPHIN (DELPHINUS DELPHIS)

Abstract: The corpora albicantia (CAs) from the ovaries of 39 common dolphins (Delphinus delphis) caught in driving fisheries were used, and histologically and immunohistochemically examined. The area of each corpus albicans (CA) and the proportion of that area occupied by elastin were measured using NIH-image software. In all CAs, elastoid material (EM) was apparent although EM area varied in each CA. CAs increased in number with dolphin age. Smaller CAs contained a higher proportion of EM. EM was completely digested b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…This was based on the following observations: CA number did not increase signifi cantly with age; pregnant D. delphis had ca 40% fewer scars than non-pregnant animals; and since all pregnant individuals were sampled between January and March, prior to the estimated calving period for the population. In contrast, studies undertaken on other populations of D. delphis, by Danil and Chivers (2007) in the eastern tropical Pacifi c, Westgate and Read (2007) in the western North Atlantic and Takahashi et al (2006) in waters off Japan have all reported a signifi cant increase in corpora number with age.…”
Section: Accumulation and Persistence Of Corpora Scarsmentioning
confidence: 68%
See 4 more Smart Citations
“…This was based on the following observations: CA number did not increase signifi cantly with age; pregnant D. delphis had ca 40% fewer scars than non-pregnant animals; and since all pregnant individuals were sampled between January and March, prior to the estimated calving period for the population. In contrast, studies undertaken on other populations of D. delphis, by Danil and Chivers (2007) in the eastern tropical Pacifi c, Westgate and Read (2007) in the western North Atlantic and Takahashi et al (2006) in waters off Japan have all reported a signifi cant increase in corpora number with age.…”
Section: Accumulation and Persistence Of Corpora Scarsmentioning
confidence: 68%
“…They were unable to differentiate CAs from pregnancy with those from ovulation, and it was assumed that smaller CAs, containing <15% elastin, were derived from infertile ovulations. With a reproductive period of ca 19 years reported for the ENA D. delphis population (Murphy et al, 2009b), results from Takahashi et al (2006) study suggest that CAs, of pregnancy at least, do persist throughout the lifetime of a female common dolphin.…”
Section: Accumulation and Persistence Of Corpora Scarsmentioning
confidence: 83%
See 3 more Smart Citations